Treatment-Resistant to Antipsychotics: A Resistance to Everything? Psychotherapy in Treatment-Resistant Schizophrenia and Nonaffective Psychosis: A 25-Year Systematic Review and Exploratory Meta-Analysis - Polese, Daniela; Fornaro, Michele; Palermo, Mario; De Luca, Vincenzo; de Bartolomeis, Andrea (Frontiers in Psychiatry, 2019)
Background: Approximately 30% of schizophrenia patients fail to respond to more than two antipsychotic trials. Psychosis has been traditionally thought to be scarcely accessible to psychotherapy. Nevertheless, there are increasing evidence that psychological interventions could be considered in Treatment Resistant Psychosis (TRP). Despite the relevance of the issue and the emerging neurobiological underpinnings, no systematic reviews have been published. Here we show a systematic review of psychotherapy interventions in TRP patients of the last 25 years. Methods: The MEDLINE/PubMed, ISI WEB of Knowledge and Scopus databases were searched from January 1, 1993 to January 1, 2018, for reports documenting on augmentation or substitution with psychotherapy for Treatment Resistant Schizophrenia (TRS) and TRP patients. Results: Forty-two articles have been found. Cognitive Behavioral Therapy (CBT) was the most frequently recommended psychotherapy intervention for TRS (studies, n=32, 76,2%), showing efficacy for general psychopathology and positive symptoms as documented by most of the studies, but with uncertain efficacy on negative symptoms. Other interventions showed similar results. Group therapy was supported by the appraised evidence. Few studies focused on negative symptoms. Results have also been reported in resistant early psychosis. Limitations: Bias due to the inclusion of heterogeneous clinical record. Conclusions: CBT, Psychosocial Intervention, Supportive counseling, Psychodynamic psychotherapy and other psychological interventions can be recommended for clinical practice. More studies are needed on treatment of resistant negative symptoms.